A model‐driven framework to enhance the consistency of logical integrity constraints: Introducing integrity regression testing. (31st October 2018) - Nooraei Abadeh, Maryam; Ajoudanian, Shohreh
Summary: Although the importance of models continuously grows in software development, common development approaches are less able to integrate the automatic management of model integrity into the development process. These critically important constraints may ensure the coherence of models in the evolution process to prevent manipulations that could violate defined constraints on a model. This paper proposes an integrity framework in the context of model‐driven architecture to achieve sufficient structural code coverage at a higher program representation level than machine code. Our framework offers to propagate the modifications from a platform‐independent specification to the corresponding test template model while keeping the consistency and integrity constraints after system evolution. To examine the efficiency of the proposed framework, a quantitative analysis plan is evaluated based on two experimental case studies. In addition, we propose coverage criteria for integrity regression testing (IRT), derived from logic coverage criteria that apply different conceptual levels of testing for the formulation of integrity requirements. The defined criteria for IRT reduce the inherent complexity and cost of verifying complex design changes in regression testing while keeping the fault detection capability with respect to the changes. The framework aims to keep pace with IRT in a formal way. The framework can solve a number of restricted outlooks in model integrity and some limiting factors of incremental maintenance and retesting. The framework satisfies several valuable quality attributes in software testing, such as safety percentage, precision, abstract fault detection performance measurable coverage level, and generality.